Hierarchical heterogeneity in mammary tumors and its regulation by autophagy. Issue 10 (2nd October 2016) - Yeo, Syn Kok; Guan, Jun-Lin
ABSTRACT: Intra-tumor heterogeneity can be attributed in part to the ability of tumor cells to acquire traits associated with less differentiated cells. In MMTV-PyMT mammary tumors, this hierarchical heterogeneity can be illustrated with the use of ITGB1/CD29 hi ITGB3/CD61 + markers to enrich for mammary stem-like cells and ALDH + to identify luminal progenitor-like cells. Macroautophagy/autophagy appears to be important for maintaining the cancer stem-like traits of both these populations. Interestingly, the regulation of these distinct cancer stem-like cells by autophagy occurs through EGFR-STAT3 and TGFB/TGF-β-SMAD pathways, respectively. These findings indicate that autophagy plays a significant role in cancer stem-like cells, and distinct cancer stem-like cells within a tumor may require different treatment modalities.